Saturday

April 19, 2014

April 19, 2014

Posted by **mo** on Tuesday, August 28, 2012 at 10:19am.

5/2.e^t-3/2.e^-t

- ODE -
**Steve**, Tuesday, August 28, 2012 at 12:48pmL{e^t} = 1/(s-1)

L{e^-t} = 1/(s+a)

L is a linear transform, so

L{5/2.e^t-3/2.e^-t} = 5/2 L{e^t} - 3/2 L{e^-t}

= 5/2 * 1/(s-1) - 3/2 * 1/(s+1)

= (s+4)/(s^2-1)

- ODE -
**mo**, Tuesday, August 28, 2012 at 3:05pmcompute the inverse laplace transform 2S^2+13S+5/(s+3)(s-1)^2

i got 3e^t+5e^t+3e^t, not sure it correct

**Related Questions**

ODE - what is the laplace transform of cost+4sint

ODE - compute the inverse laplace transform 2S^2+13S+5/(s+3)(s-1)^2 i got 3e^t+...

Math - What is the laplace transform of (t^2)sin(t)?

Calculus - Find the inverse Laplace transform of: F(s)=3/(s-4)

Calculus-HELP!!! - Find the inverse Laplace transform of: F(s)=2/s^4

calculus - Find the inverse Laplace transform of the function: F(s)=1/(s(s+1)(s+...

Calculus - Find the Laplace transform of: f(t)=t-2e^(3t)

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

advanced math - what is the Laplace transform of e^4t(cos 2t) ?